2021
DOI: 10.1007/978-3-030-85990-9_25
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review for Sentiment Analysis of Arabic Dialect Texts Researches

Abstract: People in the Arab world prefer to use their dialects in writing while using social media sites which results in generating a significant amount of texts. Sentiment analysis in texts is one of the most important applications of the Natural Language Processing field of science. Sentiment Analysis involves classifying texts based upon emotions or polarity. Different approaches have been utilized so far for Sentiment Analysis of Arabic Texts. In this systematic review, the author aims to explore the researches an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 42 publications
0
7
0
Order By: Relevance
“…The researchers also found that, when compared to other Arab world nations, the Gulf countries have the lowest Facebook usage [10]. It was also found that most researchers used the Twitter and Facebook platforms to create Arabic text datasets [6].…”
Section: Datasetmentioning
confidence: 95%
See 4 more Smart Citations
“…The researchers also found that, when compared to other Arab world nations, the Gulf countries have the lowest Facebook usage [10]. It was also found that most researchers used the Twitter and Facebook platforms to create Arabic text datasets [6].…”
Section: Datasetmentioning
confidence: 95%
“…(b) According to [40], Instagram is one of the top three social media platforms in the United Arab Emirates; Instagram is popular social media site in UAE and its popularity is increasing day after day. (c) Finally, while reviewing research papers, most of the constructed datasets used Twitter and Facebook platforms to construct datasets of Arabic texts; however, a limited number of studies targeted the Instagram platform for collecting comments and constructing datasets from the collected comments [6].…”
Section: Datasetmentioning
confidence: 99%
See 3 more Smart Citations